Does the Program Manager Matter? New Public Management and Defense Acquisition. (January 2017) - Eckerd, Adam; Snider, Keith
Past efforts to reform defense acquisition have been based in New Public Management assumptions that certain attributes of program managers (PMs), such as their training and experience levels, are important for improving outcomes. This article documents an effort to examine the relationship between such PM attributes and program outcomes using data drawn from annual Department of Defense Selected Acquisition Reports for major defense acquisition programs between 1997 and 2010. The findings provide little support for these assumptions. They point instead to the potential for institutionalist theories to explain acquisition outcomes, which can enable more nuanced reform policies in the future.